Sexual health of women using combined oral contraceptive containing estetrol and drospirenone: A prospective observational study - Mekan R. Orazov; Viktor E. Radzinskiy; Marina B. Khamoshina; Roman E. Orekhov; Vasily V. Ermakov (IP Berlin A.V., 2024)
Aim. To evaluate the effect of a combined oral contraceptive (COC) containing estetrol and drospirenone on the sexual function of women using it. Materials and methods. A total of 251 women aged 21-35 years (mean age, 25.30±2.82 years) referred for contraceptive fitting were included in the study (ICD-10: Z30.0 General contraceptive advice and counseling, Z30.4 Contraceptive drug monitoring). Women in the study cohort used the original formulation containing 15 mg estetrol and 3 mg drospirenone in a 24+4 regimen for contraceptive purposes, according to the current instructions. All female participants (n=251) were assessed for sexual function at baseline, 6 and 12 months using FSFI (The Female Sexual Function Index), FSDS-R (The Female Sexual Distress Scale-Revised) and SQoL-F (The Sexual Quality of Life-Female) scales. Study design. An open, independent, prospective observational study. Results. Women taking COC containing estetrol 15 mg and drospirenone 3 mg maintained a baseline high level of sexual satisfaction (p0.05) throughout the study, as assessed by FSFI, SQoL-F and FSDS-R scales. Conclusion. The results obtained indicate that there is no negative effect of COC containing 15 mg estetrol and 3 mg drospirenonone on the sexual function of women. High contraceptive efficacy of the drug was confirmed.